Perbandingan Tingkat Terendah Trombosit antara Pasien Demam Dengue dan Demam Berdarah Dengue - WISNU TRANAYA PUTRA; SRI MASYENI; KOMANG TRISNA SUMADEWI; SARASWATI LAKSMI DEWI (Hang Tuah Medical Journal, 2026)
Background: Dengue infection remains a major public health problem and is frequently accompanied by thrombocytopenia. The lowest platelet level during illness (thrombocyte nadir) may reflect clinical severity and assist in early risk stratification. Objective: To compare the mean thrombocyte nadir between patients with dengue fever (DF) and dengue hemorrhagic fever (DHF). Methods: A cross-sectional study was conducted using medical record data of 150 hospitalized dengue patients at Sanjiwani Hospital (2022–2024). Dengue was confirmed by IgM anti-dengue testing or NS1 antigen detection. DHF was defined as a ≥20% increase in hematocrit at admission. Patients with a history of idiopathic thrombocytopenic purpura were excluded. Demographic and clinical data were summarized descriptively, and differences in thrombocyte nadir between DF and DHF were analyzed statistically. Results: Of 150 patients, 119 (79.3%) had DF and 31 (20.7%) had DHF. The thrombocyte nadir differed significantly between groups, with DHF demonstrating a lower nadir than DF (p = 0.001). Conclusion: Thrombocyte nadir is significantly lower in DHF compared with DF, supporting the usefulness of serial platelet monitoring to aid severity assessment and clinical surveillance in hospitalized dengue patients.